ECONOMIC ASSESSMENT OF INNOVATION DEVELOPMENT OF THE REGION - Ncfu (Вестник Северо-Кавказского федерального университета, 2022)
The article describes the methodological and technical approaches to the comprehensive economic assessment of the innovative development of the region on the basis of the relationship and interdependence of performance innovation, innovation activities, innovation capabilities, innovation receptivity and effectiveness of innovation.